Opioid Use and Its Relationship to Cardiovascular Disease and Brain Health: A Presidential Advisory From the American Heart Association. Issue 13 (28th September 2021) - Chow, Sheryl L.; Sasson, Comilla; Benjamin, Ivor J.; Califf, Robert M.; Compton, Wilson M.; Oliva, Elizabeth M.; Robson, Chester; Sanchez, Eduardo J.
Abstract : The misuse of opioids continues to be epidemic, resulting in dependency and a recent upsurge in drug overdoses that have contributed to a significant decrease in life expectancy in the United States. Moreover, recent data suggest that commonly used opioids for the management of pain may produce undesirable pharmacological actions and interfere with critical medications commonly used in cardiovascular disease and stroke; however, the impact on outcomes remains controversial. The American Heart Association developed an advisory statement for health care professionals and researchers in the setting of cardiovascular and brain health to synthesize the current literature, to provide approaches for identifying patients with opioid use disorder, and to address pain management and overdose. A literature and internet search spanning from January 1, 2012, to February 15, 2021, and limited to epidemiology studies, reviews, consensus statements, and guidelines in human subjects was conducted. Suggestions and considerations listed in this document are based primarily on published evidence from this review whenever possible, as well as expert opinion. Several federal and institutional consensus documents and clinical resources are currently available to both patients and clinicians; however, none have specifically addressed cardiovascular disease and brain health. Although strategic tools and therapeutic approaches for recognition of opioid use disorder and safe opioid use are available for health care professionals who manage patients with cardiovascular disease and stroke, high-quality evidence does not currently exist. Therefore, there is an urgent need for more research to identify the most effective approaches to improve care for these patients.